Pengaruh Gaya Kepemimpinan Kepala Sekolah Demokratis Terhadap Sikap Disiplin Guru di SD N Gabus 4 Sragen Tahun 2016/2017 - Septiana, Lailla; , Dr. AchmadFathoni, M.Pd (2017)
This study aims to describe: (1)Effect of democratic leadership style of Principal to the teachers' discipline attitudes in SD N Gabus 4 Sragen. (2)The great improvement of the teachers' discipline with the leadership style of democratic Principal in SD N Gabus 4 Sragen. In this study the researcher used a quantitative approach. The technique of collecting data is questionnaireand interview. The data analysis technique used is simple regression test, t test and coefficient of determination. With research result (1)There is effect of democratic leadership style of Principal to the teachers' discipline attitudes in SD N Gabus 4 Sragen.Can be seen from the result of t test obtained by thitung for Principal Leadership Style variable equal to 7.053 while the ttabel is 2.037, and reinforced by simple regression equation Y = 15,711 + 0,594X so it can be concluded that there is significant influence between Principal Leadership Style on teachers' discipline in SD NegeriGabus 4 Sragen. (2) The great improvement of the teachers' discipline with the leadership style of democratic Principal in SD N Gabus 4 Sragen.Can be seen from the calculation of the coefficient of determination is 0.734, it can be interpreted that 73.4% change Y (Teachers' Attitude Discipline) due to the change of variable X (Principal Democratic Leadership Style) while 26.6 The remaining% is due to changes in other variables not included in this study.